Effect of brain‐derived neurotrophic factor on sperm function, oxidative stress and membrane integrity in human. (2nd May 2016) - Najafi, A.; Amidi, F.; Sedighi Gilani, M. A.; Moawad, A. R.; Asadi, E.; Khanlarkhni, N.; Fallah, P.; Rezaiian, Z.; Sobhani, A.
Summary: Oxidative stress has negative impacts on the clinical outcomes of assisted reproduction techniques. The brain‐derived neurotrophic factor (BDNF) promotes the viability of nerve cells and is known to decrease oxidative stress and apoptosis in different cells. The aim of this study was to evaluate the effect of BDNF treatment on human sperm functions that are known to be essential for fertilisation. Our findings showed that treatment of human spermatozoa with 0.133 nM BDNF significantly increased the percentages of both total ( P = 0.001) and progressive ( P < 0.01) motile sperm cells compared to those observed in the nontreated (control) group. We also showed that the mean fluorescence intensity of DCFH‐DA, as an indicator of intracellular reactive oxygen species, was significantly lower ( P < 0.05) in spermatozoa treated with BDNF compared to the control group. Treatment of spermatozoa with BDNF significantly decreased the percentages of both dead ( P = 0.001) and apoptotic‐like sperm cells ( P < 0.05) compared to the control group. On the other hand, BDNF treatment significantly increased the percentage of viable sperm cells compared to the control ( P = 0.001). In conclusion, BDNF has protective effects against oxidative stress in spermatozoa and could improve sperm functions that are essential for sperm–egg fusion and subsequent fertilisation.